Popular Islam: A Contemporary Phenomenon in Indonesia - Zully Qodir; Imron Rosidi (Asia-Pacific Journal on Religion and Society, 2019)
This article confirms that popular Islam is an emerging Islamic phenomenon in Indonesia. The rise of popular Islam is due to the symbolic understanding of Islam. This kind of Islam leads to formalism  Islam, rather than substantial ones that lead to humanity and justice. Popular Islam has been influenced a lot because of the presence of celebrity preachers and their large-scale campaigns from social media such as Instagram, Facebook, Linkedin, and Whatshap. The biggest challenge of Indonesian Islam, in addition to the rise of popular Islam, is the growth of an Islamic spirit that uses identity in politics so as to arouse Islamic radicalism and extremism. Islamic radicalism-extremism is not actually a culture of Indonesian Islam, but later developed in Indonesia.